Implementation of Parhyangan Aspects in Awig-Awig (Traditional Regulations) Subak Anggabaya - Yowana, I Made Adiwidya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Subak is often discussed as a large museum, a place where people can learn about the application of a philosophy, whose name is Tri Hita Karana (THK). That is why UNESCO recognizes Subak with the topic: Subak as Manifestation of the Tri Hita Karana Philosophy. That if you want to see how a philosophy called Tri Hita Karana is applied in society, then just look at the activities of the subak system in Bali. The Parhyangan aspect is one of the elements of the Tri Hita Karana which must be regulated in the awig-awig subak. A rule will certainly not be meaningful or useful if it is not implemented. Therefore, it is important to carry out research regarding the implementation of the parhyangan aspect in Awig-awig Subak Anggabaya. Regarding the location, the research was carried out at the Anggabaya subak as one of the sustainable subaks in the city of Denpasar. Based on this background, the problem raised is how to implement the parhyangan aspect in the awig-awig subak Anggabaya. The data is analyzed using qualitative analysis, namely the data and facts found will be described. Next, it will be studied based on existing references or based on logic. From the research results, it can be concluded that the implementation of the parhyangan aspect in the awig-awig subak Anggabaya has generally gone well.